Nonredundant functions of Arabidopsis LecRK‐V.2 and LecRK‐VII.1 in controlling stomatal immunity and jasmonate‐mediated stomatal closure. Issue 1 (18th December 2017) - Yekondi, Shweta; Liang, Fu‐Chun; Okuma, Eiji; Radziejwoski, Amandine; Mai, Hsien‐Wei; Swain, Swadhin; Singh, Prashant; Gauthier, Mathieu; Chien, Hsiao‐Chiao; Murata, Yoshiyuki; Zimmerli, Laurent
Summary: Stomatal immunity restricts bacterial entry to leaves through the recognition of microbe‐associated molecular patterns (MAMPs) by pattern‐recognition receptors (PRRs) and downstream abscisic acid and salicylic acid signaling. Through a reverse genetics approach, we characterized the function of the L‐type lectin receptor kinase‐V.2 (LecRK‐V.2) and ‐VII.1 (LecRK‐VII.1). Analyses of interactions with the PRR FLAGELLIN SENSING2 (FLS2) were performed by co‐immunoprecipitation and bimolecular fluorescence complementation and whole‐cell patch‐clamp analyses were used to evaluate guard cell Ca 2+ ‐permeable cation channels. The Arabidopsis thaliana LecRK‐V.2 and LecRK‐VII.1 and notably their kinase activities were required for full activation of stomatal immunity. Knockout lecrk‐V.2 and lecrk‐VII.1 mutants were hyper‐susceptible to Pseudomonas syringae infection and showed defective stomatal closure in response to bacteria or to the MAMPs flagellin and EF‐Tu. By contrast, Arabidopsis over‐expressing LecRK‐V.2 or LecRK‐VII.1 demonstrated a potentiated stomatal immunity. LecRK‐V.2 and LecRK‐VII.1 are shown to be part of the FLS2 PRR complex. In addition, LecRK‐V.2 and LecRK‐VII.1 were critical for methyl jasmonate (MeJA)‐mediated stomatal closure, notably for MeJA‐induced activation of guard cell Ca 2+ ‐permeable cation channels. This study highlights the role of LecRK‐V.2 and LecRK‐VII.1 in stomatal immunity at the FLS2 PRR complex and in MeJA‐mediated stomatal closure.